2022
DOI: 10.1111/sjop.12886
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the association of social anxiety with cognitive variables: The role of self‐esteem, self‐perception, fears of positive and negative evaluation, and post‐event processing

Abstract: Theoretical models of social anxiety disorder (SAD) have identified several cognitive factors (fear of negative evaluation [FNE], self-perception, selfesteem, and post-event processing [PEP]) that play a role in the maintenance of the disorder. The current study aimed at testing both the cognitive factors addressed in these different models and the fear of positive evaluation (FPE) in the same construct. A non-clinical emerging adulthood sample (N = 325) were subjected to structural equation modeling (SEM). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…Moreover, according to the current research, individuals exposed to harsh oversight are hesitant to engage in social interactions where they might feel that they are being negatively judged by others, which could worsen their psychological distress and become the reason for their loneliness (Haugen, 2023;Lampraki et al, 2022). Gök & Yalçınkaya-Alkar (2023) found that individuals with a higher dread of negative evaluation are likelier to develop poor SE. Fear about being evaluated typically comes with unpleasant experiences.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, according to the current research, individuals exposed to harsh oversight are hesitant to engage in social interactions where they might feel that they are being negatively judged by others, which could worsen their psychological distress and become the reason for their loneliness (Haugen, 2023;Lampraki et al, 2022). Gök & Yalçınkaya-Alkar (2023) found that individuals with a higher dread of negative evaluation are likelier to develop poor SE. Fear about being evaluated typically comes with unpleasant experiences.…”
Section: Introductionmentioning
confidence: 57%
“…FNE in adolescents and childhood stages disturbs the psychological and mental ability of the students and lowers their SE (Kocatürk & Çiçek, 2023). It can lead to social anxiety and, EL and lower their SE (Gök & Yalçınkaya-Alkar, 2023). According to Ho & Gu, 2023 SE is positive, and the negative attitude of individuals toward themselves (Ho & Gu, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation